Relationship between the Role of Stress on the Quality of Government Internal Audit with Knowledge Search as a Mediating Variable - Agustiawan, Agustiawan; Rahayu, Norra Isnasia; Perdana, Riky; Yusoff, Mohd Nor Hakimin bin; Abdullah, Tahirah binti (Akuntansi & Ekonomika, 2025)
This study investigates how role ambiguity and role conflict influence audit quality among government internal auditors, with knowledge seeking as a mediating variable. Public sector audit quality is crucial, yet internal auditors often experience role pressures that can weaken performance. Survey data from internal auditors in government institutions were analyzed using PLS-SEM with WarpPLS. Findings show that both role ambiguity and role conflict negatively affect audit quality. Knowledge seeking partially mediates the impact of role conflict, indicating that actively searching for information, guidance, and expertise can lessen the negative consequences of conflicting demands. In contrast, knowledge seeking does not mediate the relationship between role ambiguity and audit quality, suggesting unclear expectations and responsibilities remain a major obstacle even when auditors attempt to learn. This study contributes to public sector auditing theory and offers practical insights for competency development and capacity-building programs to improve government internal auditor performance and audit quality.